2014
DOI: 10.1016/j.egypro.2014.10.410
|View full text |Cite
|
Sign up to set email alerts
|

Smart Meters and People Using the Grid: Exploring the Potential Benefits of AMR-Technology

Abstract: The debate on the introduction of AMR (Automated Meter Reading) in Norwegian households is largely built on the assumption that users will react on price incitements in relation to electricity. However, the basic function of the AMRsystem technology is to measure the use of energy and the power output (effect) and send this information to the electricity suppliers. In the list of demands on the imminent implementation of AMR-technology it is not specified how information on the actual use and the current price… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In other words, male EFL teachers use smart board in teaching English for Palestine more than female EFL teachers do. Table (12) indicates that the value of calculated "F" is lower than the tabulated "F" which means that there weren"t statistically significant differences due to years of experiences among teachers. The data of table (13) present that the value of calculated "F" is lower than the tabulated "F" for teaching stages and for the whole part which means that there were statistically significant differences The previous table (14) indicates that there were differences in the mean of smart devices uses for the sake of secondary level teachers.…”
Section: Table6 T-test Value and Significant Level Between Male And mentioning
confidence: 82%
See 1 more Smart Citation
“…In other words, male EFL teachers use smart board in teaching English for Palestine more than female EFL teachers do. Table (12) indicates that the value of calculated "F" is lower than the tabulated "F" which means that there weren"t statistically significant differences due to years of experiences among teachers. The data of table (13) present that the value of calculated "F" is lower than the tabulated "F" for teaching stages and for the whole part which means that there were statistically significant differences The previous table (14) indicates that there were differences in the mean of smart devices uses for the sake of secondary level teachers.…”
Section: Table6 T-test Value and Significant Level Between Male And mentioning
confidence: 82%
“… Test of Hypotheses Related to the uses of Smart Board Independent samples T-test was used to find out if there are differences due to gender (male and female). One way ANOVA was used to find out if there are differences due to years of experiences (0-5, 6-10 and more than 10 years) and teaching level (elementary, preparatory and secondary stages) as its clear in tables (10,11,12) view the results. The previous table (11) presents that the computed T is higher than the tabulated T in all parts and in the total degree of the second domain of the questionnaire.…”
Section: Table6 T-test Value and Significant Level Between Male And mentioning
confidence: 99%
“…As smart grid trials have become increasingly more common, it has become clear that the task of changing passive consumers to active energy system resource managers is a tremendous challenge (e.g. Löfström 2014, Katzeff and Wangel 2015, Hargreaves, Nye, and Burgess 2013, Gangale, Mengolini, and Onyeji 2013, Buchanan, Russo, and Anderson 2015, Broman Toft, Schuitema, and Thøgersen 2014.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Results from a high number of participants, presented by OPOWER (Arlington County, VA, USA), a company that provides a large-scale, low-technology system for electricity billing in the United States, show reductions of 3% over the first two years of operation in 35,000 participants against a control group [9]. Issues related to privacy concerns could explain the unwillingness of comparing one's own electricity usage to other peers: the respondents might consider sharing their electricity usage with their neighbors as an invasion of their private life [56]. On this matter, results presented in Naus et al [57] showed that, although Dutch consumers were eager to enhance existing energy management practices cooperating with suppliers and with fellow householders, their participation in new monitoring, production and time-shifting was highly dependent on their autonomy and privacy consideration.…”
Section: Consumption Information and Feedbackmentioning
confidence: 99%